The regulating role of galectin-9 in immune cell populations - Cao, Zhanqi; Leng, Ping; Xu, Hanlin; Li, Xiangpeng (Frontiers in Pharmacology, 2024)
Galectin-9 (gal-9) is a protein that belongs to the galectin family. Gal-9 is expressed in cells of the innate and adaptive immune system, including lymphocytes, dendritic cells, giant salivary cells, eosinophils and T cells, etc. In different immune cells, the role of gal-9 is different. Gal-9 can induce the proliferation and activation of immune cells, and also promote the apoptosis of immune cells. This effect of gal-9 affects the occurrence and development of a variety of immune-related diseases, such as the invasion of pathogenic microorganisms, immune escape of tumor cells, and inflammatory response. Thus, understanding the biological roles of gal-9 in innate and adaptive immunity may be essential for autoimmune diseases treatment and diagnosis to improve patient quality of life. In this review, we aim to summarize current research on the regulatory roles of gal-9 in human immune system and potential inducers and inhibitors of gal-9, which may provide new strategies for immune diseases therapies.